Tm3Fe5O12/Pt Heterostructures with Perpendicular Magnetic Anisotropy for Spintronic Applications. (12th December 2016) - Quindeau, Andy; Avci, Can O.; Liu, Wenqing; Sun, Congli; Mann, Maxwell; Tang, Astera S.; Onbasli, Mehmet C.; Bono, David; Voyles, Paul M.; Xu, Yongbing; Robinson, Jason; Beach, Geoffrey S. D.; et al.
Abstract : With recent developments in the field of spintronics, ferromagnetic insulator (FMI) thin films have emerged as an important component of spintronic devices. Ferrimagnetic yttrium iron garnet in particular is an excellent insulator with low Gilbert damping and a Curie temperature well above room temperature, and has been incorporated into heterostructures that exhibit a plethora of spintronic phenomena including spin pumping, spin Seebeck, and proximity effects. However, it has been a challenge to develop high quality sub‐10 nm thickness FMI garnet films with perpendicular magnetic anisotropy (PMA) and PMA garnet/heavy metal heterostructures to facilitate advances in spin‐current and anomalous Hall phenomena. Here, robust PMA in ultrathin thulium iron garnet (TmIG) films of high structural quality down to a thickness of 5.6 nm are demonstrated, which retain a saturation magnetization close to bulk. It is shown that TmIG/Pt bilayers exhibit a large spin Hall magnetoresistance (SMR) and SMR‐driven anomalous Hall effect, which indicates efficient spin transmission across the TmIG/Pt interface. These measurements are used to quantify the interfacial spin mixing conductance in TmIG/Pt and the temperature‐dependent PMA of the TmIG thin film. Abstract : A bilayer system consisting of the strained ferrimagnetic insulator Tm3 Fe5 O12 and the heavy metal Pt, which possesses perpendicular magnetic anisotropy at the interface, is presented. Good spin current transparency is demonstrated at this interface that allows the observation of anomalous Hall effect and the study of the magnetic anisotropy via spin Hall magnetoresistance.